Data Analysis of Globular Cluster Harris Catalogue in View of the King Models and Their Dynamical Evolution. II. Observational Evidences - Marco Merafina; Daniele Vitantoni (Acta Polytechnica CTU Proceedings)
We summarize some observational comparison concerning the features of globular clusters (GCs) population in connection to the evolution of King models. We also make a comparison with some extragalactic GCs systems, in order to underline the effects of the main body on the dynamical evolution.